Influence of Self-Compassion, Social Support, and Living Arrangements on Subjective Well-being of the Elderly - Yufi Adriani; Siska Handika (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2023)
This research aimed to investigate the influence of self-compassion, social support, and living arrangements on the subjective well-being of the elderly. To achieve this objective, a quantitative approach utilizing Multiple Regression Analysis was employed as the research method. The study included 225 participants aged 60 years and above, residing in DKI Jakarta, Indonesia. The participants were selected using non-probability sampling techniques. The findings of the study indicated a significant impact of self-compassion, social support, and living arrangements on the subjective well-being of the elderly. The dimensions of self-compassion, namely self-kindness, common humanity, and mindfulness, as well as perceived emotional support, and living with a partner, exhibited a positive association with the variable. In addition, the combined independent variables accounted for 56.6% of the explained variance. Further research were recommended to use moderator variables between independent and subjective well-being as well as other internal or external factors such as personality, religiosity, and education level.